Methodology of Conventional Perceptions - reza Mollai (حکمت اسرا)
Real perceptions are reflections of the external world, while conventional perceptions are the product of adapting a concept to its unreal example. For this reason, considering the conventional as a perception is fundamentally accompanied by a kind of tolerance. Conventional perceptions do not have any kind of noumenal relations. The relations between conventional perceptions, or conventional perceptions and real perceptions, are subordinate to their forgery and convention. Hence, the stages of thought for obtaining conventional perceptions are different from the stages of thought for obtaining real perceptions and the method of deduction in conventional perceptions from the method of deduction in real perceptions. One can never consider a conventional perception to be the product of a real perception or other conventional perceptions. Although, in some forms of argumentation, conventional perceptions have deductive relations with each other, these relations are different from the productive relations of perceptions. The conventional argumentation is polemic. This polemic nature is not just in the matter of argumentation, but the form of argumentation is also polemic. This makes it possible to derive conclusions from conventional arguments that are primarily sterile, since the form of argumentation, like the matter of argumentation, is conventional and subordinate to the convention of convention-makers.